1996
DOI: 10.1007/bf00196561
|View full text |Cite
|
Sign up to set email alerts
|

Starch debranching enzyme (R-enzyme or pullulanase) from developing rice endosperm: purification, cDNA and chromosomal localization of the gene

Abstract: Starch debranching enzyme (R-enzyme or pullulanase) was purified to homogeneity from developing endosperm of rice (Oryza sativa L. cv. Fujihikari) using a variety of high-performance liquid chromatography columns, and characterized. A cDNA clone encoding the full length of the rice endosperm debranching enzyme was isolated and its nucleotide sequence was determined. The cDNA contains an open reading frame of 2958 bp. The mature debranching enzyme of rice appears to be composed of 912 amino acids with a predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
87
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(90 citation statements)
references
References 30 publications
3
87
0
Order By: Relevance
“…such as insensitive response of starch synthase in rice endosperm to high temperature compared with wheat endosperm (Rijven, 1986) or possible role of debranching enzymes in starch degradation (Nakamura et al, 1996) have been reported, ADP -glucose pyrophosphorylase and soluble starch synthase seem to be one of key enzymes under high-temperature stress. Further studies on the behavior of these enzymes are needed.…”
Section: Abbreviations On Figuresmentioning
confidence: 99%
“…such as insensitive response of starch synthase in rice endosperm to high temperature compared with wheat endosperm (Rijven, 1986) or possible role of debranching enzymes in starch degradation (Nakamura et al, 1996) have been reported, ADP -glucose pyrophosphorylase and soluble starch synthase seem to be one of key enzymes under high-temperature stress. Further studies on the behavior of these enzymes are needed.…”
Section: Abbreviations On Figuresmentioning
confidence: 99%
“…For this reason, and because there is a marked preference for the hydrolysis of (136)-␣-glucosyl linkages in oligosaccharides compared with polysaccharides, the enzyme is usually referred to as limit dextrinase (Lee et al, 1971). This nomenclature will be used here, although the enzyme is also referred to as the R-enzyme (Nakamura et al, 1996).As a result of the proposed role for limit dextrinases in starch hydrolysis in germinated barley grains, and because of the associated importance of this process in the malting and brewing industries, considerable effort has been directed toward the purification and characterization of the barley enzyme (Sissons et al, 1992;Longstaff and Bryce, 1993;MacGregor et al, 1994a;Kristensen et al, 1998). The enzyme has been reported in both developing (Sissons et al, 1993) and germinated grain (Kristensen et al, 1998).…”
mentioning
confidence: 99%
“…For this reason, and because there is a marked preference for the hydrolysis of (136)-␣-glucosyl linkages in oligosaccharides compared with polysaccharides, the enzyme is usually referred to as limit dextrinase (Lee et al, 1971). This nomenclature will be used here, although the enzyme is also referred to as the R-enzyme (Nakamura et al, 1996).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The function of PUL is less understood than that of ISA. PUL is believed to be associated with the degradation of starch during kernel germination; however, its activity has been detected in developing rice and maize endosperms [106][107][108], suggesting PUL may also be involved in starch biosynthesis. Loss of just PUL in maize mutants results in no significant alterations in starch structure or composition in maize endosperm, while loss of both ISA1 and PUL results in a significant accumulation of phytoglycogen in maize endosperm [109].…”
Section: Starch Debranching Enzymes (Dbes)mentioning
confidence: 99%